A Forgetten Field in the Economy of Salonica: Tobacca Production and Trade, and the Regie (1883-1912) - (:unkn) unknown (ISAM, 2014)
Tobacco has been an important agricultural product for the economy of Salonica in 19th century. Trade of tobacco, which were produced in Salonica countryside, strengthened the relationship between the Salonica economy and international markets. Regie Company participated in Salonica tobacco sector in the last quarter of the 19th century. All actors of tobacco sector, workers, merchants, other tobacco companies and especially tobacco farmers were affected -more or less- from the implementations of the Regie. This paper aims to discuss the production and trade of tobacco in Salonica before and after the Regie. The tobacco factory with its definite role in the economy of Salonica and tobacco smuggling will also be evaluated in the paper. Another issue of the paper is the activities of the koldju [guard] organization, which has been an instrument of the Regie to end the smuggling.
Keywords: Salonica; tobacco; merchant; farmer; worker; factory; tobacco smuggling; koldju [guard]; Regie